Moderating Role of Professional Commitment to Audit Quality Reduction Behavior during the Covid-19 Pandemic Period: Peran Moderasi Komitmen Profesional terhadap Perilaku Reduksi Kualitas Audit Periode Pandemi Covid-19 - Arfiana Dewi; Dwi Kartikasari, Evi (Journal of Accounting Science, 2022)
The aims of this study was to examine the effect of time budget pressure and locus of control on the behavior of auditors performing audit quality reduction behavior in the midst of the covid-19 pandemic. In addition, to find out profesional commitment to moderate the effect of time budget pressure and locus of control on audit quality reduction behavior in the midst of the covid-19 pandemic. The population in this study are auditors who work in Public Accounting Firms, the sampling method used purposive sampling and obtained a sample of 64 respondents who collected data using google form. Data analysis used multiple linear regression and moderated regression analysis (MRA). This study found that external locus of control had a positive effect on audit quality reduction behavior and the moderating role of profesional commitment was not supported. This study implies that auditors can adapt to current conditions except for auditors who have an external locus of control and policy makers can pay attention to this.